If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-2x + 2) = -9x Reorder the terms: -5(2 + -2x) = -9x (2 * -5 + -2x * -5) = -9x (-10 + 10x) = -9x Solving -10 + 10x = -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -10 + 10x + 9x = -9x + 9x Combine like terms: 10x + 9x = 19x -10 + 19x = -9x + 9x Combine like terms: -9x + 9x = 0 -10 + 19x = 0 Add '10' to each side of the equation. -10 + 10 + 19x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 19x = 0 + 10 19x = 0 + 10 Combine like terms: 0 + 10 = 10 19x = 10 Divide each side by '19'. x = 0.5263157895 Simplifying x = 0.5263157895
| -7x-3y=-7 | | 6st+9t+10s-15= | | -32-7x=4(4x-8) | | -3.6-r=(-6r+0.6) | | 4+4x-x^2-x^3=0 | | 3x-15+x=180 | | -6-2(-9x-8)=-3 | | s=q+3/x | | .40c+4-.20c=-9 | | -23=-t | | b-4c+3a-c-9b-4a=0 | | 5(6x-5)+51=-6(x-7)+18x+2 | | -8x-9+5x=-9x+3 | | x+3=5x+2 | | 4.9t^2+2.14t+42=0 | | 5F-9C=120 | | 3/2*16*1/2 | | 7/2*16*-1/2 | | .5x-2.3=0.7 | | 3x+7x+4=2x-6 | | -21.15=m-6.33-6.7m | | 15/2*64*-1/2 | | -8a-b-(-6c)-2a-b-5c=0 | | x-3/10-8=3x+2 | | 6-2x+7-3x=12 | | 2*6*w+2*w*8+2*6*8=208 | | 9x-7=9(x-5) | | 15/2((64)-1/2) | | -2c=pm^2-n | | -(x+2)=-18-x | | X-5/3=5/4 | | x/5=-23 |